Sealing ability of hydroxyapatite as a root canal sealer: in vitro study - Widowati Witjaksono; Lin Naing; Ema Mulyawati; AR. Samsudin; Mon Mon Tin Oo (Dental Journal (Majalah Kedokteran Gigi), 2007)
Hydroxyapatite (HA) is the most thermodynamically synthetic calcium phosphate cement, and has indicated useful as a sealer because can seal a furcation perforation, is shown to be biocompatible and also has potential to promote the healing of bone in endodontic therapy. The objective of this study is to determine the sealing ability of HA produced by School of Engineering, Universiti Sains Malaysia (USM) when used as a sealer in root canal obturation, compare with Tubli-seal (Zinc-Oxide base) and Sealapax (Calcium Hydroxyde base) sealers. Forty five single rooted human anterior teeth were instrumented and randomly divided into three experimental groups of 15 teeth each. All teeth in the experimental groups were obturated with laterally condensed gutta percha technique. Teeth in the first group were sealed using Zinc-Oxide (ZnO) based sealer and those of second group using Calcium Hydroxide (CaOH) based root canal sealer. Third experimental group was sealed using HA from School of Engineering USM. Teeth were then suspended in 2% methylene blue. After this, teeth were demineralized dehydrated and cleared. Linear dye penetration was determined under magnifying lense with calibrated eye piece. Statistical analyses of the linear dye penetration were performed with Kruskal Wallis test. The intergroup comparison between HA and ZnO groups and CaOH groups were analyzed by Mann-Whitney test. The dye penetration for group which were sealed with HA exhibited the lowest penetration and it showed that there was a statistically significant difference both between HA and ZnO groups and also between HA and CaOH groups (p < 0.001).In conclusion, it was found that value added HA based endodontic material which were produced by USM can be used as a root canal sealing materials when it used in combination with epoxy resin since it leaked comparatively less as compared to ZnO and CaOH sealers. Before reaching a definitive conclusion, this material requires further extensive exploration both clinically and in vitro.